2011
DOI: 10.1161/circep.111.962340
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Study of Vernakalant (Oral) for the Prevention of Atrial Fibrillation Recurrence After Cardioversion

Abstract: Background-Vernakalant, a relatively atrial-selective antiarrhythmic drug, has previously demonstrated efficacy for the acute conversion of atrial fibrillation (AF) to sinus rhythm. This study was designed to determine the most appropriate oral dose of vernakalant for the prevention of AF recurrence postcardioversion. Methods and Results-Patients with nonpermanent AF were randomized to 150, 300, or 500 mg vernakalant or placebo twice daily for up to 90 days. The efficacy analysis was conducted on 605 of 735 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…45 An oral formulation of vernakalant for the prevention of AF recurrence post-cardioversion is under investigation. 46 Our data suggest that the clinical efficacy demonstrated for vernakalant can be partly explained by suppression of triggered activity responsible for the induction of AF and other atrial arrhythmias. The effects of vernakalant to induce post-repolarization refractoriness in PV, as in other atrial tissues (Burashnikov and Antzelevitch, unpublished observation), also points to a mechanistic rationale for rhythm control utility in the chronic management of AF.…”
Section: Discussionmentioning
confidence: 71%
“…45 An oral formulation of vernakalant for the prevention of AF recurrence post-cardioversion is under investigation. 46 Our data suggest that the clinical efficacy demonstrated for vernakalant can be partly explained by suppression of triggered activity responsible for the induction of AF and other atrial arrhythmias. The effects of vernakalant to induce post-repolarization refractoriness in PV, as in other atrial tissues (Burashnikov and Antzelevitch, unpublished observation), also points to a mechanistic rationale for rhythm control utility in the chronic management of AF.…”
Section: Discussionmentioning
confidence: 71%
“…Following intravenous administration, vernakalant effectively converted AF to sinus rhythm in recent onset and postoperative AF [305][306][307]. In a recent clinical trial oral vernakalant was found to be effective for maintaining sinus rhythm following cardioversion of AF [308]. Vernakalant does not exhibit proarrhythmic effects in dogs with chronic atrioventricular block, a model featuring I Ks downregulation, bradycardia and increased susceptibility to arrhythmias [309].…”
Section: Dronedaronementioning
confidence: 99%
“…Vernakalant does not exhibit proarrhythmic effects in dogs with chronic atrioventricular block, a model featuring I Ks downregulation, bradycardia and increased susceptibility to arrhythmias [309]. No proarrhythmic adverse effects were found in a rabbit proarrhythmia model [310] or in a recent clinical trial [308]. In AF associated with HF, vernakalant appears to be less effective for cardioversion and increased incidence of serious hypotensive episodes and ventricular arrhythmias were detected in patients with left ventricular dysfunction [311].…”
Section: Dronedaronementioning
confidence: 99%
“…form of vernakalant given for conversion of AF [12][13][14][15], but yet only one such Phase II study evaluating the oral form of vernakalant is published [16].…”
Section: Pharmacokineticsmentioning
confidence: 99%